Power ... : Durham University, 13-16 July 2007 ... - Calenda (OpenEdition, 2006)
How was power exercised, implicitly and explicitly, in the centuries of the medieval and Renaissance eras? How was it displayed and performed, theorised, ritualised, romanticised, codified, sanctified or opposed? The conference will consider questions such as these in a sequence of interdisciplinary sessions covering the full span of the periods and looking at social contexts ranging from the medieval republic of Iceland to the imperial courts of Renaissance Europe. ...